The cyclicality of the separation and job finding rates in France - Jean-Olivier Hairault; Thomas Le Barbanchon; Thepthida Sopraseuth (Institute for the Study of Labor (IZA), 2012)
In this paper, we aim to shed light on the relative contribution of the separation and job finding rates to French unemployment at business cycle frequencies by using administrative data on registered unemployment and labor force surveys. We first investigate the fluctuations in steady state unemployment, and then in current unemployment in order to take into account the unemployment deviations from equilibrium. Our results show the dominant role of the job finding rate in accounting for French unemployment fluctuations. The contribution of the job finding rate amounts to about two-thirds of the unemployment dynamics. With the two data sets, we find that both rates contributed to unemployment fluctuations during the nineties, while the job finding rate has been more significant in the last decade. In particular, the last business cycle episodes, including the last recession, exacerbate the role of the job finding rate.
Keywords: E24; J6; 330; unemployment variability; job separation; job finding; worker flows; Konjunkturelle Arbeitslosigkeit; Arbeitsuche; Arbeitsmobilität; Frankreich